Russian aggression against Ukraine and the changes in European Union countries’ macroeconomic situation: Do energy intensity and energy dependence matter? - Wielechowski, Michał; Czech, Katarzyna (Economics and Business Review, 2023)
The study aims to assess whether there are significant differences among EU member states regarding the Russo-Ukrainian-conflict-driven changes in macroeconomic indicators and whether these differences are linked to the country’s energy vulnerability. Applying the k-means clustering, there are distinguished three country groups similar with regard to regarding their energy intensity, energy dependence (including Russian gas dependence) and household budgets' exposure to energy prices. Based on Kruskal-Wallis and Wilcoxon pairwise comparison tests, the study reveals statistically significant differences among the distinguished country clusters in the level of inflation and interest rates at the time of this conflict and differences in the 2022 forecasts' changes for GDP, inflation, budget balance and unemployment. The results indicate that EU economies characterised by the most significant energy vulnerability economically suffer the most in the aftermath of the Russian invasion of Ukraine.